PENGARUH PENGGUNAAN MEDIA SOSIAL INSTAGRAM @HUMASBDG TERHADAP PEMENUHAN KEBUTUHAN INFORMASI FOLLOWERS - Sutrisno, Agnes Pertiwi; Mayangsari, Ira Dwi (Jurnal Common, 2021)
Media social utilization, especially Instagram has become a focus of the Indonesian Government to use as a fulfiller of followers' information needs, almost all of the regional governments use social media to communicate with the people. It also accompanied by the continous rise of internet usage and media social usage in Indonesia. This research is done to know the influence of social media @humasbdg's Instagram utilization on the fulfillment of follower's information needs, to know the differences between male and female followers in social media utilization and to know the differences between male and female followers in the fulfillment of followers' information needs. Researcher uses quantitative research methodology by distributing questionnaire to respondents via Instagram's direct message. The population in this research are the followers of @humasbdg Instagram account. The data analysis techniques used in this research are descriptive analysis, t hypothesis test, simple linear regression analysis, determination coefficient and comparative hypothesis test. The result of the research based on the t hypothesis test, simple linear regression analysis, coefficient determination yields that media social utilization (X) have a significant positive influence on the fulfillment of followers' information needs variable (Y), media social utilization (X) have influence as big as 69.72% to the fulfillment of followers’ information needs variable(Y). While the remaining 29.28% is inluenced by other factors that are not studied in this research. The result of comparative hypothesis test using ANOVA test and Z-test on X and Y variables shows that there’s no significant difference between male and female respondents.